Perencanaan Produksi Guna Mengatasi Overstock Produk Jadi pada CV PCP - Firdaus Muswati, Awanda; Mundari, Siti (Fakultas Teknik UMRI, 2024)
CV PCP is a manufacturing company that manufactures road construction products. This company produces various types of road construction products, namely rectangular paving blocks, hexagonal paving blocks, 3D paving blocks, curbs, U-Ditch, and kerbstones. At CV PCP, the production planning and inventory control processes are less than optimal, resulting in overstock in the finished goods warehouse. The overstock problem causes storage to exceed warehouse capacity, products to be damaged due to excessive accumulation, and transportation access to be disrupted. This research addresses the overstock of finished goods in the warehouse caused by these factors. The Run Out Time (ROT) method determines the optimal production schedule by considering the production sequence based on the inventory depletion time. From the production planning using the Run Out Time (ROT) method, the average production result over 6 months before ROT was 156,600 pcs, and after the implementation of ROT, the result was 107,136 pcs. With the decrease in production output, the quantity of product stock also experienced a decline. The average product stock before the implementation of ROT was 386,681 pcs. After the implementation of ROT, it was 299,629 pcs, so the product stock did not exceed the maximum warehouse capacity of 345,000 pcs. Because overstock in the warehouse is minimized, the risk of product damage can also be minimized, which affects storage costs that decreased from an average of Rp. 81,216,828 before the implementation of ROT to Rp. 75,613,317 after the implementation of ROT. As a result, the company can also minimize the storage costs of finished products.